Which energy labels should we use to expedite the transition to electric vehicles? - Scarlat, Gal; Rosenzweig, Stav; Rubin, Ofir (Frontiers in Environmental Science, 2024)
In recent years, numerous countries have enacted legislation to halt fossil-fueled vehicle sales within five to ten years. With shrinking global markets for these vehicles, manufacturers are increasingly motivated to redirect them towards nations with less stringent regulations, using attractive prices and other tactics. However, the sale of new fossil-fueled vehicles poses a public challenge as they will remain in use for years. Consequently, reducing the likelihood of consumers purchasing new fossil-fueled vehicles in favor of electric vehicles (EVs) is crucial in all countries, particularly those with less stringent regulations, to meet emission goals. Efforts to promote EV adoption through policy measures fall short due to underestimated cognitive biases and consumer behavior impacts. We contribute to the literature by bridging the gap between human behavioral studies and environmental policy.We incorporate choice architecture into energy labels to determine which information architecture regarding energy costs is an effective nudge in increasing electric vehicle purchase intentions. Our experiment finds that labels framing energy costs as 'expenditure,' rather than 'savings,' are more effective in increasing the intent to purchase an electric vehicle. Additionally, we find that a graphical display of expenditure was not effective in influencing purchase intentions. Policymakers can use similar choice architecture tools to encourage electric vehicle adoption, expediting the transition to electric vehicles and achieving national environmental goals.